2020
DOI: 10.3390/jcm9030867
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proinflammatory, NF-kappaB Dependent Cytokines: IL-1α, IL-6, IL-8, and TNF-α in Tissue Specimens and Saliva of Patients with Oral Squamous Cell Carcinoma and Oral Potentially Malignant Disorders

Abstract: Background: Oral squamous cell carcinoma (OSCC) is a life-threatening disease. It could be preceded by oral potentially malignant disorders (OPMDs). It was confirmed that chronic inflammation can promote carcinogenesis. Cytokines play a crucial role in this process. The aim of the study was to evaluate interleukin-1alpha (IL-1α), interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor alpha (TNF-α) in tissue specimens and saliva of patients with OSCC and OPMDs. Methods: Cytokines were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 51 publications
(39 reference statements)
5
45
0
1
Order By: Relevance
“…Noteworthy, interleukin (IL)-6 and IL8 as well as tumor necrosis factor (TNF)-α contribute to the progression of OSCC [ 37 ]. In particular, IL-8 is the most important factor for malignant transformation in OSCC [ 38 ]. The phenomenon of a HIF-1α mediated stabilization under normoxia upregulating IL-1β has also been published [ 39 ].…”
Section: The Hif-1α System As a General Regulator Of Oscc Progressmentioning
confidence: 99%
“…Noteworthy, interleukin (IL)-6 and IL8 as well as tumor necrosis factor (TNF)-α contribute to the progression of OSCC [ 37 ]. In particular, IL-8 is the most important factor for malignant transformation in OSCC [ 38 ]. The phenomenon of a HIF-1α mediated stabilization under normoxia upregulating IL-1β has also been published [ 39 ].…”
Section: The Hif-1α System As a General Regulator Of Oscc Progressmentioning
confidence: 99%
“…Chuanshu et al 26 found that serum SCC‐Ag levels in OSCC (stages III + IV) were significantly higher than those in early tumors or normal subjects. A study of cytokine levels in OSCC illustrated that TNF‐α levels were significantly increased 27 . Kulkarni et al 28 demonstrated that salivary TNF‐α levels increased with the histological grade of OSCC and leukoplakia.…”
Section: Discussionmentioning
confidence: 99%
“…A study of cytokine levels in OSCC illustrated that TNF-α levels were significantly increased. 27 Kulkarni et al 28 demonstrated that salivary TNF-α levels increased with the histological grade of OSCC and leukoplakia. However, there are no clinical studies on AFP in OSCC.…”
mentioning
confidence: 99%
“…Studies showed that pro-in ammatory cytokines are produced not only by in ammatory cells, but also by tumor cells. Among which, IL-6 was widely involved 33 . In consequence, CRP level in tumor patients was logically elevated.…”
Section: Discussionmentioning
confidence: 99%